Aspects of the water use of Cannabis sativa L. under dryland cultivation in the Eastern Cape - Zenani, Kamva Trevor Songo (Rhodes University, Faculty of Science, Institute for Water Research)
Cannabis spp is one of the oldest cultivated plants, with its origin in Asia. It has two species, namely C. indica and C. sativa. This research focuses on C. sativa, which is widely cultivated locally and globally. C. sativa has a wide range of uses, including industrial, medicinal, religious, and recreational. This study will be focusing on the water use of medicinal and recreational C. sativa grown under dryland conditions. In recent years, there has been a growing interest in increasing its cultivation, but there are reports of it having high water usage. The global interest has led many governments to review the laws governing this plant as it is a controlled substance in many countries. Due to its legal status, there is a dearth of knowledge about its growth and water use. It is against this backdrop that the Water Research Commission (WRC) commissioned this study into the water use of this plant. This will provide evidence-based support for the issuing of water use licenses by the Department of Water and Sanitation. The Eastern Cape and KwaZulu Natal have many small-scale legacy farmers who have been growing C. sativa illegally for decades. The findings of this research will seek to fill some of these knowledge gaps and assist legacy farmers in the cultivation of this plant. This research had four approaches, which include 1) planting the crop in a dryland location that will mimic the conditions experienced by legacy growers, 2) the collection of plant biophysical variables in the study site in order to gain a better understanding of the plant's health, growth, progress, and to use these variables to parameterize a mechanistic eco-physiological model, 3) the installing of a large aperture scintillometer (LAS) together with a micro-meteorological station to measure the evapotranspiration (ET) and meteorological parameters over a crop cycle, 4) to use MEDRUSH evapotranspiration model to predict the ET and compare these results against that of the LAS. The results show that water provision had a significant impact on plant biophysical variables and water use. The plants received 154 mm (2 mm day-1) of rain during the crop cycle. The large aperture scintillometer recorded a total ET of 126.8 mm (1.76 mm day-1) during the same period. The MEDRUSH model (2.5 mm day-1) overestimated the LAS ET (1.79 mm day-1), and the results from the daily ET revealed that C. sativa had higher daily ET when compared to the local grass Eragrostis plana. These results confirm that at this location in the Eastern Cape, C. sativa requires regular irrigation during the growing season to grow and secure a crop.
Keywords: Cannabis; Water consumption; Large aperture scintillometer; Cannabis Water requirements; Dry farming -- South Africa -- Eastern Cape; Evapotranspiration